PENGARUH PEMAHAMAN PERPAJAKAN DAN KESADARAN WAJIB PAJAK RUMAH KOS DENGAN SANKSI PERPAJAKAN SEBAGAI VARIABEL MODERASI - Sososutiksno, Christina (JURNAL LENTERA AKUNTANSI, 2023)
This study aims to determine the effect of tax understanding and taxpayer awareness of boarding business owners in paying boarding house taxes with taxation as a moderating variable in Ambon City. Knowing taxpayer compliance is the purpose of this study and the independent variables in this study are grouped into two, namely understanding of taxation and awareness of taxpayers and tax sanctions as moderating variables. The variable in this study is taxpayer compliance in paying for a boarding house. This study uses a quantitative descriptive method. This study uses primary data obtained from questionnaires distributed to business taxpayers in the city of Ambon. And based on the respondents based on the Slovin formula, a sample of 100 taxpayers was obtained. Data analysis in this study used data analysis using multiple linear regression analysis and moderated regression analysis using Moderated Regression Analysis (MRA). The results of the moderation test using Moderated Regression Analysis (MRA) show that taxpayer awareness in tax reporting is in accordance with taxpayer compliance, while tax sanctions are not able to moderate the relationship between taxation and taxpayer compliance. Key words: Understanding Of Taxation, Taxpayer Awareness, Mandatory Compliance, and Tax Sanctions